Geminiviruses Subvert Ubiquitination by Altering CSN-Mediated Derubylation of SCF E3 Ligase Complexes and Inhibit Jasmonate Signaling in Arabidopsis thaliana - Lozano-Durán, Rosa; Rosas-Díaz, Tábata Victoria; Gusmaroli, Giuliana; Pérez-Luna, Ana Isabel; Taconnat, Ludivine; Wang Deng, Xing; Rodríguez-Bejarano, Eduardo (Oxford Academy, 2011)
Viruses must create a suitable cell environment and elude defense mechanisms, which likely involves interactions with host proteins and subsequent interference with or usurpation of cellularmachinery. Here, we describe a novel strategy used by plant DNA viruses (Geminiviruses) to redirect ubiquitination by interfering with the activity of the CSN (COP9 signalosome) complex. We show that geminiviral C2 protein interacts with CSN5, and its expression in transgenic plants compromises CSN activity on CUL1. Several responses regulated by the CUL1-based SCF ubiquitin E3 ligases (including responses to jasmonates, auxins, gibberellins, ethylene, and abscisic acid) are altered in these plants. Impairment of SCF function is confirmed by stabilization of yellow fluorescent protein–GAI, a substrate of the SCFSLY1. Transcriptomic analysis of these transgenic plants highlights the response to jasmonates as the main SCF-dependent process affected by C2. Exogenous jasmonate treatment of Arabidopsis thaliana plants disrupts geminivirus infection, suggesting that the suppression of the jasmonate response might be crucial for infection. Our findings suggest that C2 affects the activity of SCFs, most likely through interference with the CSN. As SCFs are key regulators of many cellular processes, the capability of viruses to selectively interfere with or hijack the activity of these complexes might define a novel and powerful strategy in viral infections.
Geminiviruses Subvert Ubiquitination
Keywords: Virus fitopatógenos; geminivirus; ubiquitination; jasmonate